Effect of lavender aromatherapy on the pain of arteriovenous fistula puncture in patients on hemodialysis - Mansooreh Aliasgharpour; Reyhaneh Abbaszadeh; Nooredin Mohammadi; Anoshirvan Kazemnejad (Tehran University of Medical Sciences, 2016)
Background & Aim: Arteriovenous fistula (AVF) is one of the inevitable elements in the take care of patients on hemodialysis. Pain of AVF puncture is a real problem for patients. The purpose of this study was to assess the effect of inhalation of lavender aromatherapy on pain intensity of arteriove-nous fistula puncture in patients on heamodialysis. Methods & Materials: In this before and after quasi-experimental clinical trial study, 40 patients on heamodialysis were selected using convenience sampling method. Pain intensity measured after needle insertion in AVF in two stages including without any intervention and after using lavender aromatherapy in the three consecutive heamodialysis sessions of each stage. Visual analogue scale was used to evaluate and determine pain. Repeated ANOVA test was used compare the pain before and after interventions. Results: The pain scores in two stages of without any intervention and inhalation of lavender aroma-therapy in the three consecutive heamodialysis sessions of each stage were 5.36 ± 2.08, 5.69 ± 2.29, 5.58 ± 2.15 and 4.00 ± 2.48, 3.05 ± 1.94, and 2.97 ± 2.27, respectively. There was significant differ-ences between the pain scores in first time before and first time after (P = 0.003) and first time before and second and third time after (P ˂ 0.001) and second and third time before and first, second and third time after inhalation of lavender aromatherapy (P ˂ 0.001). Conclusion: The results of study showed inhalation of lavender aromatherapy is effective to decrease pain of AVF puncture in patients on hemodialysis. Therefore, lavender aromatherapy could be a suit-able alternative complementary medicine for the pain of AVF puncture.